IMPACT OF SPECIES COMPOSITION AND ARTIFICIAL FEED ON THE GROWTH OF CARP - NANDEESHA, M C; MURTHY, C K (Fishery Technology, 2017)
Two trials conducted to demonstrate the suitability of composite carp culture in a small, seasonal, shallow village pond with varied species composition and stocking density indicated the possibility of obtaining higher production with reduced number .of species. During the first trial, the Indian major carps, silver carp, common carp and fringelipped carp were stocked at a density of 5625 fingerlings/ha in the pond in which the maximum water spread area was 1600 m 2 • The fish grown over a period of seven months yielded a production of only 242 kg. However, during the second trial, an increase in production by 60.33 % was achieved over the same period in the same pond by stocking only the Indian major carps and common carp at a density of 4687.5 fingerlings/ ha and feeding them daily with silkworm faecal matter based artificial feed at about 5 % of their body weight. The results indicated that for seasonal, shallow ponds stocking of only three species of carps, namely, catla, rohu and common carp would suffice to get optimum yield.